How Does Digitalization in the Economy Affect China’s CO2 Emissions: A Panel Data Analysis - Yuang, Zhao; Zhang, Hongwu (Energy Economics Letters, 2022)
Climate change is one of the most serious concerns confronting humanity today and is threatening the sustainability of life on Earth. Human activities over the years are responsible for rapidly degrading environmental sustainability, which has created unprecedented challenges. China's economic growth and carbon emissions have risen sharply during the past four decades. As part of the Paris Agreement, China has pledged to reduce emissions to combat global warming. In recent years, China's economic growth is trending in the direction of digitalization as a result of the rapid expansion of the internet and the rising prevalence of digital technologies. This paper examines whether digitalization can affect CO2 emissions and offers solutions for China's green economy. The cross-sectional autoregressive distributed lag (CS-ARDL) method is used to determine the impact of digitalization on CO2 emissions. The data on variables for 30 Chinese provinces were collected from the China Statistical Yearbook and China’s provincial statistics. Using the provincial data on China, we found that digitalization affects CO2 emissions in stages. In the beginning, digital technologies increase energy needs, which can impair ecological sustainability. In subsequent phases, digital finance may lower the threshold for financial services, making it easier for enterprises to secure financing, which affects production, technological progress, CO2 emissions, and the environment. Most of China's provinces are digitally modifying their economic structures and changing their company dynamics, which, in turn, affect the environment.